Ensuring Data Privacy in the Age of Artificial Intelligence - Zahra, Yatama (PT. Lentera Ilmu Publisher, 2025)
This study explores the intersection of data privacy and artificial intelligence (AI) within the context of Indonesia’s evolving digital landscape. As AI technologies become increasingly embedded in key sectors such as healthcare, finance, education, and public services, the need for robust data protection mechanisms grows more urgent. The 2022 enactment of Indonesia’s Personal Data Protection (PDP) Law marks a significant step toward safeguarding individual privacy rights and regulating the use of personal data in AI systems. However, challenges remain in ensuring compliance with legal principles such as transparency, purpose limitation, and user consent, especially as many AI models operate as opaque